Colombia and its participation in the war of Korea: A relection 64 years after the conlict started. - Meléndez Camargo, Juan David (Universidad Pedagógica y Tecnológica de Colombia, 2015)
The document is a relection on the participation of Colombia in the war of Korea and the political implications it brought to the country. Such participation generated much controversy in Colombia because this decision turned the nation into the only Latin American country that cooperated with the North American cause to defeat the expansion of communism. In this geopolitical context of the Cold War, the so called“satellite wars” began, sponsored by the United States and the former Soviet Union. The Colombian circulating press was widely relevant for this study in political history. It allowed to monitor the development of this armed confrontation from the perspective of Colombian soldiers in Korea, and to relect about what this intervention achieved for the army and the country. In general terms, the ideological race of the UnitedStates and the USSR that began after World War Second, involved many third world nations into the agitated political world order, polarizing their political relationships.